Determining Veterinary Interns’ Attitudes towards Surgical Applications using a New Scale (SAAS): Intern Attitudes of Surgery Applications - Pamuk, Kamuran; Kılıç, İbrahim (Progress in Nutrition, 2021)
Study Objectives: The aim of this study was to establish cognitive, affective and behavioral attitudes of senior veterinary students (interns) towards surgical applications by developing a new attitude scale. Methods: The questionnaire, prepared as a data collection tool, was administered to 392 interns who were senior students of six faculties of veterinary medicine in Turkey. The study data were analyzed using descriptive statistics, validity-reliability analyses, cluster analysis and ANOVA. Exploratory Factor Analysis (EFA) and Cronbach’s alpha results revealed the Surgical Applications Attitudes Scale (SAAS) to be a valid and reliable scale. The overall attitude of the students towards surgical applications was above the medium level but not at the ideal level. Results: The affective attitudes of interns in particular were more negative than their cognitive and behavioral attitudes. The cluster analysis revealed three groups of veterinary interns based on their attitudes towards surgical applications. The red group was the most negative and the green group was the most positive attitude group. Conclusion: The scale developed in this study is considered important in terms of revealing the current situation regarding surgical applications in veterinary medical education, contributing to the literature, and establishing certain standards for the relevant institutions-boards.